Vertebrate species knowledge: an important skill is threatened by extinction - Gerl, Thomas; Randler, Christoph; Jana Neuhaus, Birgit (International Journal of Science Education, 2021)
Vertebrate species knowledge, a key factor for conserving biodiversity, is a compulsory part of school curricula. This study evaluated the vertebrate species knowledge of sixth-grade German grammar school pupils (aged 11–13) to investigate the influence of socio-demographic factors (gender, size of hometown, mother tongue), personal expectations (favourite school subject, performance in biology, expected test results) and possibilities to do nature observations (favourite playing area, number of excursions to nature) on identification skills. In addition, the study examined whether schoolchildren's taxonomic knowledge changed over the years. In a species identification test, participants (N = 984) scored an average of 14.18 ± 3.82 out of 25 points. The results showed that their species knowledge was significantly influenced by their personal expectations on test performance, the school, favourite playing area, mother tongue and gender. Hometown size, the number of excursions to nature, favourite school subject and performance in biology did not significantly affect children's species knowledge. Mammals had the highest identification rates, whereas birds and reptiles were rather unknown. These results were compared with a similar dataset in 2006 indicating a 15% loss in pupils’ species knowledge within the last decade. A change in the curriculum as a reason for this decline in taxonomic knowledge is discussed.
Keywords: Species knowledge; biodiversity; biodiversity awareness; conservation; science communication